Studi In Silico: Prediksi Potensi 6-shogaol dalam Zingiber officinale sebagai Inhibitor JNK - Sri Sulystyaningsih Natalia Daeng Tiring; Yohanes Bare; Andri Maulidi; Mansur S; Fitra Arya Dwi Nugraha (Al-Kimia, 2019)
Type 2 Diabetes Mellitus (T2DM) is a metabolic disease characterized by hyperglycemia and insulin resistance. T2DM therapy against c-Jun N-terminal kinase (JNK) is one of the recovery solutions using bioactive compounds from ginger. 6-shogaol is bioactive compounds of ginger that has antioxidant properties. The purpose of this study is to analyze the potential of 6-shogaol as a JNK inhibitor. JNK protein (ID: 464Y) was obtained from Protein Data Bank (PDB) through 6-shogaol ligand (CID: 5281794) obtained from the PubChem database. Protein docking protein and ligand use Hex 8.0.0 software while visualization and analysis using Discovery Studio client 4.0. The results showed that 6-shogaol was predicted to have potential as a JNK inhibitor. Proving this by finding five amino acid residues (TRY223, LEU210, THR103 ALA214, ARG107) with an energy of -236.29cal/mol. We found the type of hydrogen bonds and the van der waals forces formed. The interaction of ligand and protein successfully inactivates JNK and stops pancreatic β cell dysfunction. 6-shogaol has pharmacological properties as a JNK,T2DM.